Detection of Cytomegalovirus (CMV) in Saliva of Congenitally Infected Neonates. (4th October 2017) - Wissel, Mark; Demmler, Gail; Gandaria, Cindy; Cravens, Stephanie; Berg, Amy; Widen, Ashley; Altrich, Michelle; Kleiboeker, Steve
Abstract: Background: Congenital cytomegalovirus (cCMV) infection is a significant, but potentially under-recognized health threat. Approximately 1 of 150 neonates in the US is born with cCMV infection, with 20% exhibiting long-term health problems due to infection. Both targeted CMV testing of newborns with failed hearing screens and universal CMV screening of all newborns have been proposed as approaches to identify infected newborns early in life. Congenital CMV infection can be diagnosed by testing a newborn's saliva, urine, or blood by CMV qPCR or culture. Dried blood spots for use in qPCR assays have been shown to be a minimally sensitive specimen. Of the three specimens that are recommended, only saliva is simple, noninvasive and easy to collect. Methods: In this study, we have validated a real-time (TaqMan) PCR assay for use in testing saliva samples from neonates for the presence of CMV. In conjunction with compatible clinical findings, a CMV positive PCR result forms the basis for a clinical diagnosis. The assay was shown to be specific for CMV, with no cross-reactivity detected for other human herpesviruses or for other human viral pathogens. Since CMV shedding levels from cCMV cases are known to be above the analytical limit of detection for the assay, and samples are collected in a nonsterile environment in which incidental CMV shedding may be present from other neonatal or pediatric patients, the reporting cutoff for this assay was set at 1000 IU/mL. Following analytical validation of the assay, stored (-80°C) residual de-identified clinical saliva samples were tested. The comparator assay was CMV cell culture, and the clinical diagnosis was used to resolve discrepant results. Results: A total of 9 saliva samples, collected at approx. 1 month of age (or earlier) were tested by both assays. Two samples were negative by both assays and 6 samples were positive by both assays. A single sample was positive by qPCR but negative by cell culture; the qPCR value for this sample was 15, 100 IU/mL. This infant had two positive urine cultures, a positive saliva shell vial culture and was clinically confirmed to have cCMV infection. Conclusion: This study suggests improved sensitivity of qPCR over CMV cell culture for identification of neonates congenitally infected with CMV. Disclosures: M. Wissel, Viracor Eurofins Laboratories: Employee,  Salary S. Cravens, Viracor Eurofins Laboratories: Employee,  Salary A. Berg, Viracor Eurofins Laboratories: Employee,  Salary A. Widen, Viracor Eurofins Laboratories: Employee,  Salary M. Altrich, Viracor Eurofins Laboratories: Employee,  Salary S. Kleiboeker, Viracor Eurofins Laboratories: Employee, Salary